2001
DOI: 10.1002/chir.10006
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional separation of [7]helicene enantiomers on Cu(111)

Abstract: The adsorption of heptahelicene, a helically shaped polyaromatic hydrocarbon (C(30)H(18)), on a Cu(111) surface was studied by means of thermal desorption mass spectrometry (TDMS) and low energy electron diffraction (LEED) at temperatures between 130-1,000 K under ultrahigh vacuum (UHV) conditions. The molecule in the monolayer remains intact up to 400 K. Above that temperature it decomposes in several steps into carbon and hydrogen, desorbing subsequently as H(2). In the saturated monolayer of the racemate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…A formation of the enantiomorphous (4-1, 2 4) phase is not observed for the racemic mixture, which saturates in a c(2 Â 4) structure [119]. Other than tartaric acid, racemic heptahelicene ( [7]H; C 30 H 18 ) forms completely different structures from the pure enantiomers on Cu(111) [122][123][124][125]. This aromatic hydrocarbon is basically a construct of seven orthoannulated C6 rings and therefore an example of a chiral molecule without a stereogenic center (Fig.…”
Section: Racemic Mixturesmentioning
confidence: 99%
“…A formation of the enantiomorphous (4-1, 2 4) phase is not observed for the racemic mixture, which saturates in a c(2 Â 4) structure [119]. Other than tartaric acid, racemic heptahelicene ( [7]H; C 30 H 18 ) forms completely different structures from the pure enantiomers on Cu(111) [122][123][124][125]. This aromatic hydrocarbon is basically a construct of seven orthoannulated C6 rings and therefore an example of a chiral molecule without a stereogenic center (Fig.…”
Section: Racemic Mixturesmentioning
confidence: 99%
“…[9] Therefore, we studied the pattern formation on the Cu(111) surface, where at coverages below 95 % of the saturated monolayer the molecules are observed to diffuse readily even at lower temperatures. [10] The absence of close-packed structures up to very-high coverages is not unexpected for [7]H since the molecule has no chemical groups capable of directional intermolecular bonding. Therefore, the attractive intermolecular forces are expected to be very weak.…”
mentioning
confidence: 96%
“…The adsorption of racemic [7]H led to the formation of enantiomorphous mirror domains, in which the enantiomers are partially separated. [10] Depending on the enantiomeric excess, the local structures in those domains exhibited minute differences. Herein, however, we focus on the enantiopure structures, in which the expression of chirality goes beyond the formation of mirror domains.…”
mentioning
confidence: 99%
“…While on nickel surfaces no extended ordering phenomena has been found [24][25][26], a pronounced transfer of chirality into mono-and multilayered structures, manifested by the formation of extended chiral motifs, was observed for the pure enantiomers on Cu(111) [27,28]. Interestingly, mirror domains have been observed for the racemate at the same surface, indicating at a first glance a lateral resolution of the enantiomers [29]. However, STM experiments in combination with molecular modeling calculations (MMC) showed that heterochiral M-P pairs become aligned in a chiral zigzag configuration (Fig.…”
Section: Helical Aromatesmentioning
confidence: 77%
“…Synthesis and enantiomeric separation (e.e. > 99.9 %) of heptahelicene ( [7 ] H) has been performed as described previously [29,48]. The absolute configuration was assigned with a high level of confidence by comparison of experimental and calculated VCD spectra [49].…”
Section: Methodsmentioning
confidence: 99%